FUNGI AS BIO-INDICATORS OF AIR QUALITY: Life Science-Botany - K.N. GAIKWAD; M.D. SONAWANE (International Journal of Life Science and Pharma Research, 2012)
Air is most vital component of environment without which nobody can survive. One can survive without food for weeks, for a few days without water, but hardly for few minutes without air. Today it is a well established fact that bacteria, viruses, fungi and pollen grains cause air pollution. These biological agents are called as Biopollutants and presence of biopollutants indicates the air quality. The plants, animals and human beings are affected by air-pollution including biopollution which is responsible for causing diseases besides being allergic to them. Among the Biopollutants, in India 90% of counts of air-borne biota belongs to fungi (Agraval and Shivpuri). With the above view the aeromycoflora of K.T.H.M. College campus, Nashik was carried out for six (6) consecutive months, using Rotorod Air Sampler during the period Aug.2004 - Feb. 2005. A total count of 25 fungal spore types and 4 other types were identified from samples obtained. The average percentage contribution of each spore group is Deuteromycotina (62.85%), Basidiomycotina (21.72%), other types (10.80%), Ascomycotina (2.94%) and Zygomycotina (1.69%). The pathogenic and allergic spores recorded are Aspergillus, Cladospores ,Rhizopus,Alternaria,Helminthosporium Smuts, pollen grains, etc.